Bibliometric Study of the Development Map of Qur'an and Health Studies in the Scopus Database - Nisa, Fathimah Khoirun; Nurrohim, Ahmad; Nirwana, Andri; Azizah, Alfiyatul; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
Purpose: The focus of this study is to understand the pattern and direction of development in the study of the Qur'an and health in publications listed in the Scopus index. Methodology: This study utilizes bibliometric analysis methods to investigate all works recorded in the Scopus database on the Qur'an and Health from 1981 to 2023. The collected data was analyzed using Excel and R/R-Studio programs. VOSviewer is used to perform visual analysis of keywords and document citations. Results: The results found by the authors are several 238 publications that fit the function, subject, and criteria set. The results of this study showed an annual growth rate of 5.88% with the most publications on the Qur'an and Health in 2020. Malaysia is the biggest publisher with affiliations from the International Islamic University Malaysia. Abooul-Enein, B.H., Al-Rowais, N., and Isgandarova, N. became the most prolific writers on the theme of the Qur'an and Health. This analysis is limited to Scopus data and does not use international or nationally based-data. Applications/Originality/Value: This study briefly outlines the literature available to researchers in the field of the Qur'an and Health.